STUDI TENTANG KONTRIBUSI MUSYAWARAH GURU MATAPELAJARAN (MGMP) PKN PADA PENINGKATAN KUALITASKEGIATAN BELAJAR MENGAJAR BIDANG STUDI PKN DI SMANEGERI 2 SAMARINDA - Eka Selvi Handayani (Teacher Training and Education Faculty, Widya Gama Mahakam Samarinda University, 2016)
National development in the field of education is an effort to educate the nation and build the Indonesian people to improve the quality of Indonesian human. National development in the field of education as well as the nation's efforts to create a generation of potential, competence, excellence and competitiveness in the world of work. In order to improve the teaching skills of teachers through training, we need a container for teachers in order to always be able to share knowledge, experience and information, whether it is through communication or consultation among fellow teachers. How does the teacher do a learning activity which requires several approaches and methods targeted, and can improve learning outcomes. This type of research used in this research is descriptive, after knowing the data for observations and the results of the activities MGMPs then the data were analyzed descriptively. Activities subject teachers Civics deliberations held on a monthly basis with a specific work program. The work program covers all the problems faced Civics teachers in the process of teaching and learning activities. In an effort to increase the quality of teaching and learning activities MGMPs Civics have contributed in terms of 1. Socialization preparation of the SBC. 2. Preparation of the syllabus SBC. 3. Preparation of instructional media. 4. Determine SKL KKM. 5. Develop the RPP. 6. Exploitation learning model Civics. 7. Analysis of the results of the evaluation. 8. Deepening Civics material. 9. classroom action research. 10. Preparation compose about UTS / semester. 11. Evaluation of work.